Rural off-farm incomes in Myanmar’s dry zone - Zu, A Myint; Khine, Htet Htet; Win, Khin Zin; Kyaw, Sithu (Michigan State University, 2017)
Our study offers the following important findings relating to off-farm incomes in the Dry Zone: 1. Off-farm activities are a major source of income. Only 31% of Dry Zone income is generated directly from farming; off-farm self-employment is equally as important. Non-farm enterprises account for 20% of income, and remittances 15%. 2. Agriculture is central to rural employment. Fiftyeight percent of working-age individuals consider farming or agricultural labor to be their primary occupation, and agricultural labor is by far the most important secondary occupation. 3. Women and men work off-farm in similar numbers, but men earn higher wages. The gender wage gap is most pronounced in casual employment. There is less gender disparity in wages for non-farm work than for on-farm work. 58% of non-farm enterprises are run by women. 4. Non-farm enterprises are growing rapidly. Since 2011, the numbers of retail stores more than doubled, agricultural trading and processing trebled, and rental services providers more than quadrupled. Non-farm income is the most important source of startup capital for these businesses. 5. Most of businesses are self-operated microenterprises. The vast majority hire no labor. The rural non-farm economy is not yet a major provider of jobs, other than to business proprietors themselves.